PERAWATAN PADA MESIN BELT BUCKET ELEVATOR 51BE45 DI PT SEMEN BATURAJA (PERSERO) TBK MELALUI HASIL VIBRASI - Nan Agung, Anugerah; Safaruddin, Safaruddin (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2023)
Gastritis is an inflammatory condition of the gastric mucosa which can be acute and chronic due to the patient's lack Based on the results of the implementation of practical work activities and the discussion of the practical work report on Maintenance on 51BE45 Bucket Belt Elevator Machine at PT Semen Baturaja (Persero) Tbk Through Vibration Results with Maintenance methods that are more often used in the Mechanical Maintenance Department at Factory II Baturaja, PT Semen Baturaja (Persero) Tbk is Preventive Maintenance. Implementation of maintenance inspections on the 51BE45 Belt Bucket Elevator machine is carried out once a week and grease lubrication on bearings is carried out once every 2 weeks. Maintenance on the 51BE45 Belt Bucket Elevator machine uses tools namely Vibration Scanmeter, Infared Thermometer Gun and Grease Gun. Vibration and temperature checks are carried out on Input and Output on the gearbox unit as well as on Fixed and Loose in Pulley Head Bearings. In checking vibration, 3 directions are carried out, namely Axial, Horizontal and Vertical. Vibration checks use the international standard reference, ISO 10816-3.